Optimization of Surface Roughness of AISI 1040 Stainless Steel in Milling Process Using Taguchi Method - Neslihan Özsoy; Murat Özsoy (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Surfaceroughness significantly affects the work efficiency and life of machine partsinteracting with each other. There are many parameters that affect surfaceroughness such as processed material, cutting tool, cutting parameters, coolingtype. For this reason, optimization of the machining parameters and properprocessing conditions are very important. In this study, the optimum machiningconditions were determined by investigating the surface roughness of the milledAISI 1040 steel alloy depending on the feed per tooth (0.08 mm/tooth, 0.12mm/tooth, 0.16 mm/tooth, 0.20 mm/tooth), spindle speed (2000 rpm, 3000 rpm,40000 rpm, 5000 rpm) and the cooling type (liquid, air) parameters. The Taguchiexperimental design method was used to help achieve results at acceptablelevels and to save time and cost in achieving optimal results. Experimentsdesigned with the Taguchi method were based on the L16 orthogonal array andsignal / noise (S/N) ratios were used in the evaluation of the experimentalresults. The optimum levels of the control factors for minimizing the surfaceroughness using S/N rates were determined. The optimal conditions for surfaceroughness were observed at A1B1C2 (i.e.,feed per tooth=0.08 mm/tooth and 2000rpm spindle speed, cooling type=liquid). Variance analysis was also conductedin the study. According to the results of analyses, it was found that spindlespeed was the most significant parameter for surface roughness. Finally,confirmation tests were conducted to check the success of the optimization.